AN OFF-RECORD POLITENESS STRATEGY IN COMMISSION III OF THE DPR RI ON PREMEDITATED MURDER OF BRIGADIER J - Dwi Santoso; Ratu Shafira Nurfitria (Ikatan Dosen Menulis, 2023)
This paper aims to find out the kind of off-record strategies uttered by the participants in The Hearing Meeting (RDP), with a focus on Brown and Levinson's (1978) theory. This study's data analysis techniques include watching the video, transcribing, translating, categorizing, and classifying the data into a politeness strategy. The researchers are interested on the murder case of Brigadier Novriansyah Yosua Hutabarat or Brigadate J at Inspector General Ferdy Sambo's official residence. The video transcripts from the meeting were analyzed, and the researchers found 10 out of 15 techniques off record politeness strategies uttered by the participants of the hearing meeting and forms of politely.